Situation Report of European Club Football (2017 – 2019) - Bács, Bence András (International Journal of Engineering and Management Sciences, 2021)
The most professional and profit oriented sector of the sports industry is football. International summary analyzes of the sector show a steady increase in revenue over the last 20 years. Yet the real turning point in terms of the profitability of European club football was in 2017, when the aggregate result of the clubs playing in the top European leagues were realized as a profit. However in recent years, the sector has faced serious competitors. The esport industry draws attention to itself with the growth rate of the base of its’ followers and related revenues. Also the fitness sector outperformed the football sector in 2019. In this article I reviewed european football between 2017 and 2019, in order to explore the characteristics of the football sector, to ascertain its revenue-generating capacity, its change in its revenue structure, and to answer the questions that if this sport will maintain its dominant position in the European sports market. My research method was document analisys of annual reports published by UEFA and Deloitte, which allowed me to examine data from more than 700 clubs in 55 countries. In overall it can be stated that the european football industry is maintaining it’s position, but it should allocate resources to stabilize its follower base instead of fearing the endagerment by other sports.